Pengaruh Profitabilitas, Aset Pajak Tangguhan, Perencanaan Pajak, dan Leverage Terhadap Manajemen Laba - Putri, Diana; Nuryati, Tutty; Rossa, Elia; Marinda Machdar, Nera (CV. Lafadz Jaya, 2023)
The purpose of this study was to determine and analyze the theory that explains the effect of profitability, deferred tax assets, tax planning and leverage on earnings management. This research uses the literature review method. This study presents a theoretical basis, other explanatory variables and the results of previous studies. The theory underlying this research is agency theory. The mapping of other explanatory variables that affect earnings management consists of profitability, deferred tax assets, tax planning and leverage. These results show different relationships between profitability, deferred tax assets, tax planning and leverage on earnings management so that no agreement is reached. This study provides more insight to explain the phenomenon that occurs.